Early diagenesis of sulfur in Bornholm Basin sediments: The role of upward diffusion of isotopically "heavy" sulfide. (15th November 2021) - Liu, Jiarui; Pellerin, André; Antler, Gilad; Izon, Gareth; Findlay, Alyssa J.; Røy, Hans; Ono, Shuhei; Kasten, Sabine; Turchyn, Alexandra V.; Jørgensen, Bo Barker
Abstract: Sediment-hosted marine sulfur cycling has played a significant role in regulating Earth's surface chemistry over our planet's history. Microbially-mediated reactions involving sulfur are often accompanied by sulfur isotope fractionation that, in turn, is captured by sulfate and sulfide minerals, providing the opportunity to track changes in the microbial utilization of sulfur and thus the marine sulfur cycle. Studying sulfur diagenesis within the Bornholm Basin, Baltic Sea, we explore the interplay between carbon, sulfur and iron, focusing on the fate of sulfur and the dynamics of the sulfur and oxygen isotopic response as a function of the varying thickness of the organic carbon-rich Holocene Mud Layer (HML) across the basin. Using a one-dimensional reaction-transport model, porewater sulfate and sulfide profiles were used to calculate net sulfate reduction rates (SRR) and net sulfide production rates, respectively. These calculations suggest a positive relationship between the thickness of the HML and net rates of sulfate reduction and sulfide production. Given that ascending sulfide is enriched in 34 S relative to that produced in-situ, a heightened sulfide flux promotes spatially variable precipitation of 34 S-enriched pyrite (δ 34 S ≈ −10‰) close to the sediment–water interface. Modeling results indicate that this isotopically "heavy" sulfide is formed as a consequence of mixing between ascending sulfide (up to +6.3‰) and that produced in-situ (ca. −40‰). Further, we show that the sulfur and oxygen isotopic composition of porewater sulfate is controlled by the net SRR: when the net SRR is high (i.e., in sulfide-replete settings) the downcore increase in δ 18 OSO4 is dampened relative to increase in δ 34 SSO4, whereas when net SRR is low (i.e., in iron-rich parts of the basin) downcore δ 18 OSO4 values increase while δ 34 SSO4 values remain invariant. We conclude that sedimentation rates and open system diffusion strongly influence the distribution of sulfur species and their sulfur isotopic composition, as well as the oxygen isotopic composition of sulfate, through the interaction between iron, sulfur and methane. This work highlights the importance of considering diffusion to better understand open system diagenesis and the δ 34 S signatures of sulfate and sulfide in both modern settings and ancient rocks.